Integrated Soil Fertility Management Strategies for Resilient Soils in Ethiopia - Agegnehu, Getachew; Legesse, Gizachew; Tigabie, Abiro; Desalegn, Henok; Desta, Gizaw (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Soil fertility depletion and nutrient mining are critical challenges to sustainable crop production in Sub-Saharan Africa (SSA). Addressing these issues requires a multifaceted approach, including improved soil management practices, the use of organic fertilizers, and the adoption of sustainable agronomic practices. Integrated soil fertility management (ISFM) is one of the approaches to improving the yields of crops while preserving sustainable and long-term soil health and fertility through the combined application of fertilizers, recycling of organic resources, use of responsive crop varieties, and improved agronomic practices, which minimize nutrient losses and improve the nutrient-use efficiency of crops (Agegnehu and Amede, 2017; Vanlauwe et al., 2015). The fertility status of steep-slope cultivated lands has been depleted due to the loss of soil organic matter and nutrient reserves. The response of such soils to the application of nutrients is low, unless their fertility is restored through the adoption of an integrated soil-crop system for improved crop-nutrient response and yield (Minh et al., 2023).